GE_GERICHTE P/24248/2017 vom 25. Mai 2020 - GE Cour de justice (2020)
CLASSEMENT DE LA PROCÉDURE;PLAINTE PÉNALE;PERSONNE MORALE;COLLECTIVITÉ PUBLIQUE;VIOLATION DE DOMICILE;DÉLAI;EXHIBITIONNISME;RETRAIT(VOIE DE DROIT) | CP.194; CP.386; CP.31; CP.33; CP.30; CPP.319; CPP.426